Effects of different water levels, light intensities and durations of shading on growth and development of young Tongkat Ali (Eurycoma longifolia Jack) - Rowshanaie, Hooman (2019)
In this study, the effect of different levels of irrigation water, light intensities and durations of shading on growth and development of young Tongkat Ali (TA; Eurycoma longifolia Jack) was considered. Large cultivation of TA is still very lacking due to insufficient and inconclusive information of its agronomic cultivation requirements; thus, over collecting from the tropical rain forests for commercial production of traditional medicines will ultimately endanger and lead to the species extinction. In order to sustain the continuous supply of plants raw material for industrial production, there is an urgent need to determine the essential growing requirements of this plant for the establishment of plantations of TA, particularly, in the nursery. Hence, three experiments were conducted to examine the agronomic requirements: Water levels, light intensity and shading duration of young TA. The first experiment was laid down out a Randomized Complete Block Design (RCBD) with five watering regimes imposed onto 6-month old TA seedlings from Hulu Langat, Selangor, Malaysia, namely at 125%, 100%, 75%, 50% and 25% of field capacity (FC), placed in six blocks. The main objective of the study was to evaluate the effect of different levels of irrigation water on growth and development of TA, especially the root growth and its relationship with the shoot growth. There were obvious differences among young TA seedlings for sensitivity to water stress due to the different levels imposed. Growth parameters also decreased with increasing severity of water scarcity, although by the end of the experiment, they were not significantly different under treatment 75% FC compared to non-water stress, especially in total biomass and total leaf area. Root parameters, especially root length, root diameter, root volume and specific root length (SRL) by end of the experiment demonstrated noticeable differences among young TA seedlings treated with different water levels. In the second experiment with the main objective to determine plant responses to the interaction between water availability and various light intensities on growth and development of TA, especially the root growth, the combined treatments were arranged using RCBD with a split plot layout consisting of 2 factors of three different light intensities (no cover, 50% shading, 70% shading) and three different water treatments (100% FC, 75% FC, 25% FC) blocked three times. Results showed that plant growth parameters including plant height, stem diameter and total biomass were reduced only by light scarcity condition and root/ shoot ratio; meanwhile, height ratio was higher in 70% shading compared to 50% shading and the control conditions. After 4.5 months of combined light and water treatments, seedlings exposed to 50% shading combined with 75% FC (moderate water stress) recorded the highest values for total plant leaf area (TLA; 331cm²), specific leaf area (SLA; 134 cm²/g), chlorophyll concentration (CHL; 42.6 µmol/m²) and nitrogen balance index (NBI; 22.1) compared to 70% shading imposed with water stress at 25%FC showing lower values for TLA (16.7 cm²), SLA (31.7 cm²/g), CHL (17.3 µmol/m²) respectively. Likewise, there were parallel decreasing trend in root parameters (root length, root diameter, root volume and SRL) with non-shaded plants resulting in fine root with decreased root density, which severity escalated (decreased by 46%) with decreasing light intensity at 70% shading compared to non-shaded condition. The second experiment clearly demonstrated the effect of light sensitivity of young TA seedlings, especially on root density, and this sensitivity became severe when plants were further imposed with water deficit. The third experiment investigated plant light requirement based on the duration of 50% shading imposed for 45, 30 and 15 days after start of treatment and combined with three different water treatments (100% FC, 75% FC, 25% FC). Treatments were laid out in a split plot arrangement based on RCBD with three blocks with the objective to investigate the effect of different duration of 50% shading on root system, and the morphological and physiological traits of TA. Results from the experiment showed that there were recognizable differences among young TA seedlings exposed to shading duration and water treatments. The decrease in shading duration from 45 to 15 days seemed to have increased both the peroxidase (POX) and malondialdehyde (MDA) in both root and shoot parts compared with 30 days shade duration treatment. Similarly, plants imposed with 45 and 15 days shading also recorded decrease in plant height (4%~8%), shoot diameter (2%~8%), root length (2%~8%) and root diameter (15%~20%) compared with 30 days of shading duration. The root also seemed to be more sensitive than the shoot to both POX and MDA under either too short (15 d) or too long shading duration (45 d). In the present study, the role of peroxidase in the growth of TA seedlings was examined by relating plant height, stem diameter and root parameters, in particular root length and root diameter, with peroxidase activity, which indicated that reduction in peroxidase activity was associated with the tallness and thickness of the plant, which correlated with root length and root diameter with significant correlation, such that, 30 days shading duration exhibited highest value in shoot and root parameters compared with other shade durations. Conversely, plants exposed to short duration of shading treatment (15 d  longer exposure to sunlight) exhibited greater values of MDA and POX than those exposed to 45 d shading duration with 1.2% increase in MDA in both root and shoot, and in case of POX with 33% increase in root and 20% increase in shoot, respectively. In a nutshell, even though long time shading has negative effects on growth and development, short time shading duration led to excess light intensity and has more detrimental effects. In conclusion, by evaluating the effects of different levels of irrigation water, various light intensities and different durations of shading on root and shoot traits, morphologically, physiologically and biochemically, the 50% shading at 30 d duration combined with water at 75% FC seemed to give the optimum growth and development condition for establishment of TA seedlings.